Delineation of buried stream channels using geophysical techniques - Biedler, Murray W (Rhodes University, Faculty of Science, Department of Geography, 1994)
This study sets out to evaluate the use of geophysical methods for delineating buried stream channels, which can act as zones of preferential flow within a less hydraulically conductive aquifer. This information is important for gaining an understanding of flow dynamics of alluvial systems. The most reliable method of delineating the dimensions of aquifers is by drilling, which is an expensive proposition and is best preceded by a preliminary geophysical study to help define target zones for a drilling program. The study area is located adjacent to the Coerney River in the Sundays River Valley. Geologically it consists of approximately 5 metres of alluvial fines, covering 3 metres of coarse cobbles and boulders, all underlain by alternating siltstone and sandstone beds of indeterminate thickness. Throughout the area the water is very shallow at approximately 2 metres depth and the groundwater tends to be very saline. An air photo study revealed an old oxbow channel that had been covered over by subsequent agricultural land use. The geophysical methods available for the study were portable seismic refraction, electrical resistivity and electromagnetics. Preliminary field tests clearly showed that seismics did not produce valid results. The methods of electrical resistivity and electromagnetics produced good data and were subjected to further assessment. A grid was surveyed over the study area and both geophysical methods were applied at regularly spaced stations. Soil samples were taken over the same survey grid and analyzed for electrical conductivity in a soils laboratory. The results were compared to the geophysical data in an attempt to quantify the relationship between geophysical response and soil salinity. The data from the electromagnetic survey showed areas of low electrical conductivity which was a possible indication of zones of preferential groundwater flow. A transect of boreholes was drilled over selected electrical conductivity lows and successfully intersected the buried stream channel. A comparison of the borehole logs with the layered earth models from the Vertical Electrical Soundings indicated that the electrical resistivity method was not responding to the features of the buried stream channel and the cobblestone layer. This proved the electromagnetic method to be more valuable for this particular study
Keywords: Stream channelization; Seismic refraction method; Electric prospecting; Electromagnetism; Aquifers -- South Africa; Groundwater; Hydrogeology -- South Africa